Bronchoscopic findings of flexible bronchoscopy: a one-year retrospective study in a tertiary care hospital - Antony, Philips; Deshmukh, Hafiz (International Journal of Research in Medical Sciences, 2018)
Background: Since the introduction of the first flexible fiberoptic bronchoscope by Shigeto Ikeda in 1966, fiberoptic bronchoscopy (FOB) has been a valuable tool in the diagnosis of pulmonary diseases. Therefore, the aim of this study is to report our one-year experience with the yield of flexible fiberoptic bronchoscopy at MGM Medical College and Hospital, a tertiary hospital in Maharashtra. Methods: A retrospective study of fiberoptic bronchoscopy (FOB) was performed at MGM Medical College and Hospital, Aurangabad, Maharashtra during the period 2015-2016. Bronchoscopy was performed and collection of bronchial washing, bronchial brushing, bronchial biopsy and transbronchial needle aspiration was done. Results: Out of 192 patients, 140 were males and 52 were females. Majority of them were in age group 50-59 years. Main indication was pulmonary tuberculosis. Bronchial washings were done in 168 cases and brushing in 56 cases and common location for both was right upper lobe; bronchial biopsy was done in 90 cases with commonest location left main bronchus. Transbronchial needle aspiration was done in 4 cases, active bleed was seen in 6 cases and purulent discharge was seen in 24 cases. Bronchoscopic finding in majority of patients was normal tracheobronchial tree. Conclusions: The optimal use of conventional bronchoscopy and its techniques in the hands of experienced respiratory interventionists, with the adherence of the international guidelines for performing these techniques will improve the diagnostic outcomes of those patients with the least morbidity and mortality, employing better therapeutic strategies, and thus improving the overall management of those patients.